Influence of design parameters on the short-circuit ruggedness of SiC Power MOSFETs - Romano, Gianpaolo; Riccio, Michele; Maresca, Luca; Fayyaz, Asad; Castellazzi, Alberto (2016)
This work aims to present an investigation on short-circuit (SC) failure behaviour of SiC Power MOSFETs due to the onset of thermal runaway. As inferable from experimental outcomes, it is related to the formation of hotspot, whose exact location is mainly unpredictable and dictated by device structure and design parameters non-uniformities. TCAD simulations were performed to examine the impact of some parameters mismatch on hotspot formation and failure occurrence